„Beneš-Dekrete“ von einer rechtlich historischen Perspektive - Jaromír Tauchen (Journal on European History of Law, 2024)
This article provides an objective historical analysis of the decrees issued by the President of the Republic, commonly referred to as the "Beneš Decrees." These decrees, which encompassed various legal aspects, gained attention due to their connection to the post-World War II expulsion of the German population from Czechoslovakia. The article examines the historical facts associated with these decrees, their impact on restitution disputes, and the decisions of the Constitutional Court of the Czech Republic. It also addresses the myths and simplifications surrounding the Beneš Decrees and aims to present an unbiased understanding to foreign readers.